Human Factors Studies to Assess the Usability of the Faricimab Prefilled Syringe - Barakat MR; Kwong Jr HM; Marcon G; O'Leary OE; Paris LP; Schneider P; Tang Y; Graff JM (Clinical Ophthalmology)
Mark R Barakat,1,2 Henry M Kwong Jr,2,3 Gelson Marcon,4 Olivia E O’Leary,4 Liliana P Paris,5 Petrick Schneider,4 Yannan Tang,5 Jordan M Graff2,6,7 1Retina Macula Institute of Arizona, Scottsdale, AZ, USA; 2Department of Ophthalmology, University of Arizona College of Medicine – Phoenix, Phoenix, AZ, USA; 3Associated Retina Consultants, Phoenix, AZ, USA; 4F. Hoffmann-La Roche AG, Basel, Switzerland; 5Genentech, Inc., San Francisco, CA, USA; 6Barnet Dulaney Perkins Eye Center, Phoenix, AZ, USA; 7Ophthalmology Division, Creighton University School of Medicine, Phoenix, Arizona, USACorrespondence: Jordan M Graff, Barnet Dulaney Perkins Eye Center, Phoenix, AZ, USA, Tel +1 480 843 1868, Email JGraff@BDPEC.comPurpose: Faricimab, the first bispecific antibody designed for intraocular use, is approved for the treatment of neovascular age-related macular degeneration (nAMD), diabetic macular edema (DME), and retinal vein occlusion (RVO). Here, we report the usability of a novel faricimab 6 mg pre-filled syringe (PFS) configuration that has been designed specifically for intravitreal use.Patients and Methods: A simulated-use human factors validation study enrolling 15 retina specialists and 15 ophthalmic assistants was conducted in a market research facility configured to represent an ophthalmology clinic. Participants’ ability to complete tasks related to package handling, dose preparation, and injection of a faricimab 6 mg dose into a polymer eye using the PFS was assessed. In a second Phase 3b, single-arm, actual-use study, the ability of seven retina specialists and six ophthalmic assistants to prepare and administer the PFS in accordance with the instructions for use was assessed. Injections were performed into single eyes of 35 patients with nAMD or DME in three US clinics and patients were followed for 7 days for safety reporting (ClinicalTrials.gov identifier: NCT05569148).Results: In the simulated-use study, most retina specialists and ophthalmic assistants completed all tasks deemed essential for PFS preparation and administration correctly and without error. Of the 22 tasks, the pass rate was 86.7– 100%; 16 tasks had a pass rate of 100%. No use errors were observed during the actual-use study. One patient experienced one mild adverse event of eye irritation that resolved the same day and was deemed unrelated to the study drug.Conclusion: Participants were able to safely and correctly prepare and administer a faricimab 6 mg dose using the PFS in accordance with the instructions for use, under realistic conditions representing the real world. The faricimab 6 mg PFS may therefore offer a more convenient, safe-handling alternative to vial administration.Keywords: intravitreal injection, medical device, retina specialist, human factors validation study, anti-vascular endothelial growth factor therapy